New product development Epurse application / Ain Amalina Mat Zanggi, Norsaliha Abd Hadi and Azefa Ahmad - Mat Zanggi, Ain Amalina; Abd Hadi, Norsaliha; Ahmad, Azefa (2018)
In today-world, smartphone has become important part of everyday life. As it has become more affordable, the number of smartphone users has increased dramatically. The quantity of smartphone consumers surpassed 1 billion in 2012 and predictably it will reach 1.75 billion in 2014 (eMarketer, 2014) . Along with smartphone production, plenty of services have been created to utilize the possible functions of smartphones. Not only smartphones are used as communication devices, but also to be used as socialized tool, entertainment tool, internet access tool, and even payment tool (Rajgopal, 2012) . Thanks to technology, mobile users can nowadays use their smartphones to make money transaction or payment by using applications installed in the phone. Besides payment, people can also store receipts, coupons, business cards, bills...in their smartphones. When smartphones can function as leather wallets, it is called "Digital Wallet" or widely known as "Mobile Wallet".